Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

y=3(x-2)(x-5) standard form?

Sagot :

Answer:

  • y = 3x² - 21x + 30

Step-by-step explanation:

Given is the factored form of a quadratic function.

The standard form is:

  • y = ax² + bx + c

Open parenthesis to convert it into standard form:

  • y = 3(x - 2)(x - 5)
  •   = 3(x² - 7x + 10)
  •   = 3x² - 21x + 30

Answer:

  • 3x² - 21x + 30

Step-by-step explanation:

Keep in mind that the equation in standard form is y = ax² + bx + c

[Where "a, b, and c" are the constants.]

Simplify the distibutive property:

⇒ y = 3(x - 2)(x - 5)

⇒ y = (3x - 6)(x - 5)

Simplifying the R.H.S using the rule (a + b)(c - d) = ac - ad + bc - bd:

⇒ y = (3x - 6)(x - 5)

⇒ y = (3x² - 15x - 6x + 30)

⇒ y = (3x² - 21x + 30)

⇒ y = 3x² - 21x + 30

If possible, reorganize the equation in standard form:

⇒ y = 3x² - 21x + 30 (In standard form)